Sāmudrikāsāraṃ : oru paḻaya bhāṣāvyākhyānattōṭukūṭiyatȧ - Śaṅkaran Naṃpūri, Mukkōla (Tiruvanantapuraṃ Malayāḷagṟanthāvali ;, 1969)
Palmistry; Sanskrit verse in Malayalam script, with commentary in old Malayalam.